Effects of an Informal Energy Exhibit on Knowledge and Attitudes of Fourth Grade Students - David Goodman (Intelektual Pustaka Media Utama, 2015)
The public has limited knowledge of renewable energy technologies. An increase in energy literacy can potentially lead to desired energy-related behavioral changes in the future. One potential solution is to increase the public’s access to renewable energy information by placing informal energy education exhibits in libraries, community centers, and parks. After calibrating the exhibit based on observations of children’s interactions at a children’s museum, the exhibit was displayed at a university, a private school, and a community center. The opinion surveys and interviews both showed that participants enjoyed and learned from the exhibit. Students showed no significant statistical improvement between the pretests and posttests, but interviews showed that they could recall facts, explain processes, and make inferences from the exhibit. Fourth-grade students can benefit from interacting with an informal energy exhibit in order to increase their knowledge of energy topics and technologies.